Descriptive Analysis of Sports Tourists in Spain - Rojo Ramos, Jorge; Gómez Paniagua, Santiago; Martín Carmona, Rubén; Vega Muñoz, Alejandro; Manzano Redondo, Fernando; González Becerra, María José; Adsuar, José Carmelo; Morenas Martín, Jesús (e-Motion: Revista de Educación, Motricidad e Investigación, 2022)
Sports tourism is a decisive factor in geographical mobility for leisure purposes. These activities entail certain acts and consequences inherent in their execution, which are worthy of study from the perspective of sustainable and reasonable tourism. Previous studies tried to show the characteristics of this type of tourist but did not provide relevant information to offer the necessary services to provide, to understand their patterns of habits, and to be able to act correctly. This paper aims to study the profile of the sports tourism consumer. Data provided by the National Institute of Statistics for the year 2019 was analyzed, taking a sample of 1496 people for statistical analysis. From these statistical analyses, key information on consumer profiles can be gleaned. Findings showed that people with Spanish nationality predominate, being mainly men. Both sexes show that they are over 40 years of age, with higher education, mostly married, cohabitation with a partner with children at home, with permanent employment contracts and certain patterns of behavior such as the use of their private car, and staying mainly in hotels or aparthotels. Therefore, from the point of view of sustainable tourism, it is vital to draw up profiles and patterns of consumers of this tourism, to evaluate and study its ecological, environmental, and social impact, as well as taking the appropriate measures to balance the balance between sports tourism and sustainability.